MANAJEMEN KEPALA SEKOLAH MENINGKATKAN KOMPETENSI PROFESIONAL GURU TEKNIK KOMPUTER JARINGAN - Sarah Persadanta Ginting (Manajer Pendididikan, 2015)
The general objective of this study was to describe the management of principal to improve professional competence of computer technology teacher. This study is qualitativedescriptive study. Subjects in this study are the principal, the vice principal of curriculum, and three teachers of computer technology teacher. Data collection techniques used in this study; observation, interviews, and documentation studies. Analysis of the data used 4 phases, namely data collection, data reduction, data presentation and conclusion or verification. The result of this research showed that principal have the program of management to improve professional competence of computer technology teacher, appropriate with management competence and supervision competence as a principal.Key word: management, competence, professional.